Psychocorrection of Impaired Emotional Sphere in Servicemen with Neurotic and Psychosomatic Disorders: A Psycholinguistic Analysis - Shevchenko, Rosina (East European Journal of Psycholinguistics, 2015)
This article presents the scientific concept of the mechanism of formation and functioning of the system of adaptive reactions of the person, it also considers their rational and irrational character. It also presents an interpretation of the perception of the world picture of a separate subject through psychosemantics. We consider some psycholinguistic mechanisms of formation of an individual’s system of values. We will reflect on certain regularities of formation of associative field, depending on the type of peculiarities of the psyche, i.e. personal experience, etc. The value for the process of its formation of learned clichés will also be considered, as well as the influence of upbringing received by a person, their education and social environment. The features of emotional disorders in servicemen depending of type of social, economic, personal components are addressed in this article. It reflects the results of studies of servicemen with neurotic and psychosomatic disorders using a questionnaire by Ch.D. Spielberger – Y.L. Hanin: patients with neurotic disorders differed by a high level of anxiety state and moderate levels of anxiety trait; patients with psychosomatic disorders – high levels of both anxiety state and anxiety trait. It reflects the mechanism of usage of psychocorrectional events of psycholinguistic component in the overall system. As a result the observed patients mastered the linguistic component of the pathogenic psychosomatic effects of word-concepts on the level of anxiety. They trained to weaken braking using psycholinguistic methods of pathological behavioral models, to understand the nature of their condition, to form a rational response. They were trained to recognize in their condition the predisposition to respond irrationally to situations of a certain type, activate defense mechanisms in the perception of certain stimuli.ReferencesAdler, A. (2002). Ocherki po Individualnoy Psihologii [Essays on individual psychology].Moscow: Cogito Tsentr.Glozman, J. (2002). Obschenie i Zdorove Lichnosti [Community and Individual Health].Moscow: Academy.Horney, K. (1937). The Neurotic Personality of Our Time. N. Y.: W. W. Norton andCompany, Inc.Kon, I. (1984). Lichnost i Yeio Samosoznanie [In Search of Self: Personality and HisIdentity]. Moscow: Politizdat. Maruta, N. (2000). Emotsionalnyie Narusheniya pri Nevroticheskikh Rasstroystvah[Emotional Impairments and Neurotic Disorders]. Kharkiv: Arsis.Mykhailyk, O. (2010). Psihoterapevtichna korektsIya patologiyi psihosomatichnogopohodzhennya vnaslIdok porushennya protsesu adaptatsiyi do navchannya u vIyskovihformuvannyah [Psychological adjustment pathology of psychosomatic origin due to abuse of theprocess of adaptation to training in military formations]. Medical Psychology, 5, 3(19), 26–29.Morozov, A. (2000). Delovaya Psihologiya [Psychology of Business]. S.-Petersburg:Union.Petrenko, V. (1983). Vvedenie v Eksperimentalnuyu Psihosemantiku [Introduction toExperimental Psychosemantics]. Moscow: Moscow University.Psihoterapevticheskaya Entsiklopediya [Psychotherapeutic Encyclopedia] (2006). B.Karvasarsky. (ed.). S.-Petersburg: Piter.Psihologiya [Psychology] (2003). N. Krylova, (ed.). Moscow: Academy.Shmelyov, A. (1983). Vvedenie v Eksperimentalnuyu Psihosemantiku [Introduction toExperimental Psychosemantics]. Moscow: Moscow University.